Factors Influencing Muslim Investors to Invest in Sharia Stocks during the Covid-19 Pandemic - Aqida Shohiha; Martini Dwi Pusparini; Ulfi Sheila Pinasti (Journal of Islamic Economics Lariba, 2022)
There had been a notable increase in the number of capital market investors in 2020 and 2021 as compared to previous years. In 2020, the number of investors increased by 56.21% from that of the previous year in 2019, and in 2021 it increased to 92.99% as compared to the number in 2020. Such considerable increase was surprising despite the outbreak of Covid pandemic throughout those years, which had an impact on the downturn of community's economy, as seen from an increase in the amount of unemployment by 7.07%, and a poverty rate of 9.8%. Likewise, Indonesia experienced negative economic growth in the quarter II and III of 2020. This study aims to find the factors that influence investors in making investment decisions amidst pandemic conditions that took place in 2020 and 2021 with the variables of Financial Literacy, Influencer’s Influence, Social Media Influence, social environment, and religiosity. It was obvious that these 5 factors had an influence on investment decisions, with the Financial Literacy factor as the factor that had the greatest influence and significance with a regression coefficient of 0.721.